Exploring the impact of operational efficiency on performance: Case of basic industry 2023-2024 - Nunik Nurmalasari (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2025)
This study analyzes the impact of operational efficiency on the financial performance of basic industry companies listed on the Indonesia Stock Exchange (IDX) during the period 2023-2024. Operational efficiency is measured using the BOPO ratio, while financial performance is proxied by Return on Assets (ROA). The sampling technique employed involves companies from various basic industry sectors, with data analyzed through linear regression analysis. The results indicate that operational efficiency has a significant negative effect on financial performance, evidenced by the regression equation Y = 64.761 – 0.638X and a coefficient of determination (R²) of 0.612. This means that 61.2% of the variation in financial performance can be explained by changes in operational efficiency. The findings highlight that higher operational efficiency, reflected by a lower BOPO ratio, correlates with better financial performance, emphasizing the importance of managing operational costs to improve company profitability.